HPV-negative oropharyngeal carcinoma as a separate prognostkally unfavorable form of cancer, requiring new approaches to treatment (case report) - A. R. Gevorkov; A. V. Boyko; A. P. Polyakov; L. V. Bolotina; N. N. Volchenko; I. V. Rebrikova; A. М. Lemeshko; S. V. Shashkov (Опухоли головы и шеи, 2019)
The study objective is to demonstrate the difficulties associated with treatment of HPV-negative oropharyngeal cancer.Material and methods. A 52-year-old male patient visited a doctor in P.A. Herzen Moscow Oncology Research Institute in January 2017 with complaints of pain in the right part of the oropharynx irradiating to the right ear and difficulties with swallowing food and liquids. The patient was diagnosed with stage IVA oropharyngeal cancer (cT3N2bM0).Results. The patient underwent a course chemoradiotherapy (CRT); as a result, the tumor in the area of the right tonsil became indeterminable 2 weeks later. Three months after completing the course of CRT, the patient underwent modified radical right-sided lymph node dissection. Histological examination revealed metastases from poorly differentiated squamous cell carcinoma in 3 lymph nodes (LNs) with an invasion into adjacent adipose tissue. In October 2017, we received a histological confirmation of ongoing tumor growth in the area of the tongue root and LN metastases in the left side of the neck (yrpT4aN2cM0). We performed resection of the mandible, tongue, soft tissues of the oral floor, and right side of the oropharynx with installation of an oropharyngeal stoma, extended radical left-sided neck lym-phadenectomy with excision of soft tissues (levels I—V), defect repair using an autologous pectoral musculocutaneous flap, and tracheostomy. In March 2018, the patient was found to have continuing tumor growth in the area of the epiglottis and floor of the oral cavity. The patient underwent laryngectomy with oropharyngeal resection and end tracheostomy. In July 2018, we again received a histological confirmation of tumor growth in soft tissues of the anterior neck. We performed resection of the tumor and soft tissues with subsequent plastic reconstruction of the defect. In October 2018, the patient presented with multiple metastases in both lungs. He received a course of immune therapy. Positron emission tomography revealed neoplastic foci with pathological metabolic activity in the area of the alveolar process of the mandible (left side), soft tissues of the neck, lungs, left-sided axillary LNs, and mediastinal LNs. It was decided to continue immune therapy.Conclusion. HPV-negative oropharyngeal cancer requires an optimized treatment algorithm and, possibly, more aggressive therapeutic measures, such as increased radiation doses. Both overall management strategy and recommended standard scheme of CRT should be revised; the role of surgical and chemotherapeutic components of treatment should also be reassessed. We believe that surgical intervention should be considered regardless of the effect of radiation therapy, while the duration of follow-up after CRT should be reduced.